2002
DOI: 10.1034/j.1600-0501.2002.130505.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β, tumor necrosis factor‐α levels and neutrophil elastase activity in peri‐implant crevicular fluid

Abstract: The aim of this study was to determine interleukin-1beta (IL-1beta), tumor necrosis factor-alpha (TNF-alpha) levels and neutrophil elastase (NE) activity in peri-implant crevicular fluid (PICF) of smoker and nonsmoker patients, and to investigate their relationships with clinical parameters. A total of 42 endosseous root-form dental implants of 14 patients were clinically examined by modified Plaque index (PI), modified Gingival index (GI) and probing depth (PD). Smoking habits of the patients were recorded. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
97
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 44 publications
16
97
1
1
Order By: Relevance
“…It was confirmed that higher concentrations of TNF-α, IL-17 and IL-1β are present in PICF collected from peri-implantitis-affected sites, compared to healthy controls (Ataoglu et al 2002;Curtis et al 1997;Darabi et al 2013;Vieira et al 2013;Severino et al 2011), whereas the opposite was the case for anti-inflammatory cytokine IL-10 (Casado et al 2013). More recently multiplex cytokine arrays have been applied in the analysis of PICF, allowing for a broader simultaneous screening of multiple inflammatory cytokines and chemokines.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…It was confirmed that higher concentrations of TNF-α, IL-17 and IL-1β are present in PICF collected from peri-implantitis-affected sites, compared to healthy controls (Ataoglu et al 2002;Curtis et al 1997;Darabi et al 2013;Vieira et al 2013;Severino et al 2011), whereas the opposite was the case for anti-inflammatory cytokine IL-10 (Casado et al 2013). More recently multiplex cytokine arrays have been applied in the analysis of PICF, allowing for a broader simultaneous screening of multiple inflammatory cytokines and chemokines.…”
mentioning
confidence: 65%
“…However, the presence of a specific SNP does not necessarily translate into higher levels of IL-1β in PICF (Lachmann et al 2007;Jansson et al 2005;Melo et al 2012). Although there is good evidence of the involvement of IL-1β as a crucial mediator of the host inflammatory response in peri-implant tissues (Murata et al 2002;Salvi et al 2010;Ataoglu et al 2002), this needs to be complemented with further interventional studies, whereby IL-1β inhibitors are part of the treatment. Moreover, other members of the IL-1 family, such as IL-18, which may display differential regulation from IL-1β, should also be considered in PICF (Hamedi et al 2009;Bostanci et al 2009).…”
mentioning
confidence: 99%
“…Studies have shown that a variety of inflammatory biomarkers (e.g., IL-1β, IL-6, and immunoglobulins) are present in the UWS of patients with oral and systemic disorders [17][18][19]. Therefore, the noninvasive assessment of UWS may yield valuable information and can be used to monitor the severity of oral inflammatory conditions, including peri-implantitis [17,20]. IL-1β and IL-6 are the most common inflammatory cytokines that enhance bone resorption by increasing osteoclastic activity [18].…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical markers in peri-implant crevicular fluid may indicate peri-implantitis in early stage, allowing efficient intervention before substantial amounts of bone are lost. Some biochemical markers have been suggested to detect peri-implant disease (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%